Relations between exponential laws for spaces of C∞-functions - Peter Biström (International Journal of Mathematics and Mathematical Sciences)
In this paper we prove that some new as well as some already existing exponential laws for spaces of C∞- and holomorphic functions can all be generated from one general exponential law.